Nous pratiquons, donc nous sommes? - Freeman, John (University of Dijon, 2013)
We Practice, Therefore Are We? Is part provocation and part confession. Writing from a quarter-century perspective gained in the UK and Australia, its author suggests that practice-led research in university theatre has become problematic in terms of achievement; the ways in which knowledge and understanding are articulated; how ideas of truth are bought and sold; and how research significance is sidestepped as easily as alternative methodologies. In arguing that this leads to a concern with career-orientation that takes lecturers away from face-to face contact with students the chapter exposes ways in which university foci follows funding and research methodologies are reduced to fashion-following rather than fitness for purpose.